Tanggung Jawab Orang Tua Terhadap Pendidikan Agama Dan Kemampuan Membaca Al-Qur’an Anak - RIZKAN SYAHBUDIN (At-Ta'lim : Media Informasi Pendidikan Islam, 2015)
The three institutions as a basic determinant of child development education, ie informal, formal and informal, but clearly the basis basik child is informal institutions, because these institutions where the role of parents is very big influence on a child's development in the future. Prophet Muhammad laid the foundation of a child's educational development in the hadith: "كل مولود يولد على الفطره فابواه يمجسانه اوبهودانه اوينصرانه" Every child born is holy, the parents who make it Jewish, or Zoroastrian or a Christian" means how big the influence of attention, attitudes, and actions of their parents in the formation and development of character within the child. Therefore the responsibility of parents is highly demanded in the process of integral human development.  The Qur'an is the holy book that contains instructions for mankind in this world that covers various aspects. "The Koran is the Most Great repertory which includes treasury of human culture, especially the spiritual teachings. The Qur'an is a book of education and teaching in general and also the book of social education, moral and spiritual in particular ".